Proceedings of the Seventh Annual ACM/IEEE International Conference on Human-Robot Interaction 2012
DOI: 10.1145/2157689.2157720
|View full text |Cite
|
Sign up to set email alerts
|

'Midas touch' in human-robot interaction

Abstract: Interpersonal touch is said to have significant effects on social interaction. We used the ultimatum game to examine whether touch from a robot could inhibit a negative feeling to the robot. We set two experimental conditions: the one was "touch condition" in which unfair proposals were offered to a participant when a robot touched his/her arm and the other was "no touch condition" in which unfair proposals were offered when the same robot did not. We compared Medial Frontal Negativity (MFN) measured by EEG, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Preliminary research indeed suggests that when people receive a touch from a robot, the perceived levels of trust and friendship with the robot increase [42,60,95,98,118]. Moreover, a touch made people more willing to carry out a monotonous task [95,118] and unfair monetary offers that were proposed by the robot were perceived as less unfair after being touched [42]; examples of a Robotic Midas Touch effect. Conversely, supposedly comforting touches that accompanied soothing words from a robot did not attenuate physiological stress responses while watching a scary movie, strengthen the bond with the robot, increase the perceptions of its humanlikeness, or increase one's pro-social behavior [135].…”
Section: Social Touch and The Modulating Effect Of Bonding In Human-rmentioning
confidence: 96%
See 2 more Smart Citations
“…Preliminary research indeed suggests that when people receive a touch from a robot, the perceived levels of trust and friendship with the robot increase [42,60,95,98,118]. Moreover, a touch made people more willing to carry out a monotonous task [95,118] and unfair monetary offers that were proposed by the robot were perceived as less unfair after being touched [42]; examples of a Robotic Midas Touch effect. Conversely, supposedly comforting touches that accompanied soothing words from a robot did not attenuate physiological stress responses while watching a scary movie, strengthen the bond with the robot, increase the perceptions of its humanlikeness, or increase one's pro-social behavior [135].…”
Section: Social Touch and The Modulating Effect Of Bonding In Human-rmentioning
confidence: 96%
“…Since social robots employ similar haptic technologies, it is suggested that robot-initiated touches should be able to induce similar effects as humaninitiated touches [130,131,135]. Preliminary research indeed suggests that when people receive a touch from a robot, the perceived levels of trust and friendship with the robot increase [42,60,95,98,118]. Moreover, a touch made people more willing to carry out a monotonous task [95,118] and unfair monetary offers that were proposed by the robot were perceived as less unfair after being touched [42]; examples of a Robotic Midas Touch effect.…”
Section: Social Touch and The Modulating Effect Of Bonding In Human-rmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that touch is a bi-directional modality in nature and the envisioned smooth and intuitive interaction between humans and robot implies complex interaction patterns in order to humanize robots. For example, it has been reported that a robot's touch reduces feelings of unfairness and enhances persuasiveness [76,77].…”
Section: Future Work and Concluding Remarksmentioning
confidence: 99%
“…Focusing more on the effects of touch, Fukuda et al indicated the possibility that robots can have a social effect on humans by touching them [7]. According to the results of their study, it tended to be more acceptable for humans for a robot to make a profit when the robot touches us than when the robot it does not.…”
Section: Social Effects On Human-robot Interactionmentioning
confidence: 99%